1998
DOI: 10.1001/jama.280.8.714
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Exposure and Risk of Lens Opacities in a Population-Based Study

Abstract: Context.-Exposure to UV-B radiation in sunlight has been shown to increase the risk of cataract formation in high-risk occupational groups, but risk to the population has not been quantified.Objectives.-To determine the ocular exposure to UV-B radiation in sunlight for a population of older persons and to determine the association between UV-B and lens opacities.Design.-The Salisbury Eye Evaluation project, a population-based cohort of older adults.Setting.-Salisbury, Md.Participants.-A total of 2520 community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
2
5

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(158 citation statements)
references
References 27 publications
(51 reference statements)
4
147
2
5
Order By: Relevance
“…[2][3][4] It is also high in mountainous regions with excessive UV irradiation as well as in populations in the temperate regions exposed occupationally to excessive sunlight. Several previous studies have suggested that an excessive incidence of cataracts in such areas is due to the photo-oxidation of the tryptophan residues in the lens proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] It is also high in mountainous regions with excessive UV irradiation as well as in populations in the temperate regions exposed occupationally to excessive sunlight. Several previous studies have suggested that an excessive incidence of cataracts in such areas is due to the photo-oxidation of the tryptophan residues in the lens proteins.…”
Section: Discussionmentioning
confidence: 99%
“…1 This phenomenon helps to explain the higher incidence of cataracts in areas of the world with a relatively higher dose of solar radiation reaching the earth. [2][3][4] Such a photocatalytic generation of reactive oxygen can be initiated by exposure to visible, as well as the ultraviolet (UV) frequencies, of the solar radiation. The quantum yield of such species is expected to be much higher on irradiation with UV frequencies of relatively lower wavelengths because of their higher photon energy, which is considered adequate to elevate the molecular oxygen from its ground triplet state to the singlet state by direct energy transfer.…”
Section: T Is Well Known That the Pathogenesis Of Cataracts Ismentioning
confidence: 99%
“…Eye disorders such as cataracts, age-related macular degeneration, pterygium and photokeratitis have been shown to be sun related [5]. Cataracts are a major public health problem, being the primary cause of blindness in humans [6]. Skin cancer is a major health problem that can be reduced through minimisation of UV exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of suggestions that have been made to reduce ocular exposures to solar UV radiation are the wearing of sunglasses and hats 1,5 .…”
Section: Introductionmentioning
confidence: 99%